2016
DOI: 10.3390/s16040500
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Arc Fault Detector for Early Detection of Electrical Fires

Abstract: Arc faults can produce very high temperatures and can easily ignite combustible materials; thus, they represent one of the most important causes of electrical fires. The application of arc fault detection, as an emerging early fire detection technology, is required by the National Electrical Code to reduce the occurrence of electrical fires. However, the concealment, randomness and diversity of arc faults make them difficult to detect. To improve the accuracy of arc fault detection, a novel arc fault detector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 43 publications
(50 reference statements)
0
46
0
Order By: Relevance
“…Some time-frequency analysis methods, such as a short-time Fourier transform [15], wavelet transform [11,[16][17][18][19][20][21][22], and Hilbert-Huang transform [23], have also been used for fault arc detection. In addition, some pattern recognition methods have been used to help classify the situation when an arc fault occurs, such as support vector machines [13] and neural networks [11,[20][21]23]. Most of the above methods need to extract the current characteristics under the arc fault condition based on the current waveform at the time of the arc fault and determine whether an arc fault has occurred.…”
Section: Volt-ampere Characteristics Of An Arcmentioning
confidence: 99%
See 1 more Smart Citation
“…Some time-frequency analysis methods, such as a short-time Fourier transform [15], wavelet transform [11,[16][17][18][19][20][21][22], and Hilbert-Huang transform [23], have also been used for fault arc detection. In addition, some pattern recognition methods have been used to help classify the situation when an arc fault occurs, such as support vector machines [13] and neural networks [11,[20][21]23]. Most of the above methods need to extract the current characteristics under the arc fault condition based on the current waveform at the time of the arc fault and determine whether an arc fault has occurred.…”
Section: Volt-ampere Characteristics Of An Arcmentioning
confidence: 99%
“…More studies have used frequency domain analysis methods. A harmonic analysis has been conducted on a specific frequency band of the line current when arc faults occur [10][11][12][13][14]. Some time-frequency analysis methods, such as a short-time Fourier transform [15], wavelet transform [11,[16][17][18][19][20][21][22], and Hilbert-Huang transform [23], have also been used for fault arc detection.…”
Section: Introductionmentioning
confidence: 99%
“…An arc is a luminous discharge of electricity across an insulating medium, usually accompanied by the partial volatilization of the electrodes [5,6,8]. Owning to the current flowing in the circuit and the high temperature, arcing is one of the main causes of electrical fires.…”
Section: Series Arc and Its Characteristicsmentioning
confidence: 99%
“…It was also confirmed that the series arc faults in a circuit occur due to partial disconnection between cords, loose connection between cord and terminal, and loose connection between outlet and plug. Most of the existing studies about series arcs use the carbon graphite-copper electrode specified in UL 1699 and IEC 62606 to generate the arc signal [5,6,8]. It is an ideal condition, under which the magnitude of arc current is much higher than that of the actual series arc and can be easily detected.…”
Section: Series Arc and Its Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation